Crystal structure of cyclohexylammonium thiocyanate - Bagabas, Abdulaziz A. (Acta Crystallogr E Crystallogr Commun, 2015)
In the title salt, C(6)H(11)NH(3) (+)·SCN(−), the cyclohexylammonium ring adopts a slightly distorted chair conformation. The ammonium group occupies an equatorial position to minimize 1,3 and 1,5 diaxial interactions. In the crystal, the components are linked by N—H⋯N and N—H⋯S hydrogen-bonding interactions, resulting in a three-dimensional network.